Periodontal conditions, low birth weight and preterm birth among postpartum mothers in two tertiary health facilities in Uganda - Muwazi, Louis; Mugisha Rwenyonyi, Charles; Nkamba, Moses; Kutesa, Annet; Kagawa, Mike; Mugyenyi, Godfrey; Kwizera, Godfrey; Okullo, Isaac (BMC oral health, 2014)
Literature reports have indicated an increase in research evidence suggesting association between periodontal disease and the risk of pre-term birth (PTB) and low birth weight (LBW). Periodontal diseases in Uganda have been documented as a public health problem, but their association to adverse pregnancy outcomes is unknown. This study was conducted to assess the association between periodontital diseases in postpartum mothers and PTB and LBW of babies in Mulago and Mbarara referral hospitals. Methods: This was a cross sectional study using medical records, clinical examination and oral interview of mothers at the two tertiary health facilities. Mothers with singleton babies from Mulago (n = 300) and Mbarara Hospital (n = 100) were recruited for the study. The women were clinically examined for periodontal disease by 2 trained and calibrated dentists. Data on PTB and LBW were retrieved from medical records. The data were analyzed to determine the relationship between the four parameters for periodontal disease (bleeding gingiva, periodontal pockets, gingival recession and calculus with plaque deposits) and the adverse pregnancy outcomes. Frequency distribution was used to describe the data. Bivariate and multivariate analyses were used to study the association between the periodontal diseases and adverse pregnancy outcomes. Results: Approximately 26% and 29% of the postpartum mothers examined had bleeding gingiva and periodontal pockets of 4 mm or more deep, respectively. Advanced periodontitis i.e. pocket depth ≥ 6 mm was recorded in 13 (3.6%) of the mothers. Calculus with plaque deposits were recorded in 86% (n = 343) of the mothers. Gingival recession was recorded in 9.0% of the mothers and significantly and directly related to birth weight (p < 0.05). Conclusion: Periodontal conditions of postpartum mothers in this study were found to be better than previously reported amongst the Ugandan population. Bivariate analysis showed a significant association only between gingival recession and low birth weight. However, this finding should be interpreted with caution as it could have occurred by chance.
Keywords: Preterm birth; Low birth weight; Periodontal disease